Alternative Neutralizers for Acid Mine Wastewater: Characterization and Neutralizing Potency of Pond Ash and Concrete Sludge - Awfa, Dion; Azizah, Rifka Noor; Imami, Ahmad Daudsyah; Utami, Resarizki; Army, Edo Kharima; Narita, Evi Eri; Anugrah, Muhammad Meiko Cahya; Putra, Nasrul; Prayogo, Wisnu; Novriadi, Novriadi (International Journal of Marine Engineering Innovation and Research, 2025)
One of the most widely used fuels is coal, where the South Sumatra region is an area with coal potential whose production is still being increased. On the other hand, there are negative impacts caused by coal exploration activities, one of which is mining runoff, commonly called acid mine drainage. Acid mine drainage has a low pH and contains inorganic constituents such as iron and manganese. Therefore, proper and optimum information processing is needed to support environmentally friendly mining management. In contrast, alternative materials such as blast furnace slag, wood ash, fly ash, cement kiln dust, and construction waste are being used. These materials are effective against AMD, at a relatively low cost, and outperform traditional neutralizers. However, comparing them with conventional agents is challenging due to limited data and experimental variation. In this study, the objectives to be achieved are 1) to determine the quality conditions of AMW at the study location, 2) to determine the effectiveness of the use of chemical and alternative compound neutralization agents in the processing process, and 3) to provide recommendations for the dosage, type of neutralization agent, and the most optimum time in AMW processing. The AMW obtained is then subjected to laboratory analysis related to quality, including TSS, pH, Fe, and Mn parameters. In addition, conventional and alternative neutralization agents are also prepared and then used to process AMW. Then, experiments were carried out on variations in the type of neutralization agent, the dosage of neutralization agent use, and the contact time between the neutralization agent and AMW. Experimental results have shown that these materials, mainly pond ash and concrete sludge, can effectively neutralize pH and reduce Mn concentrations by up to 83.26% and 79.12%, respectively. Similarly, Fe concentrations can be reduced by up to 80.76% and 74.05% using pond ash and concrete sludge, respectively. While these results are promising, future research should focus on characterizing the generated sludge to confirm the adsorption of ferrous and manganese ions onto the surface of the alternative neutralizers.